1970
DOI: 10.1002/pol.1970.150080210
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization initiated by an electron donor–acceptor complex. Part IV. Kinetic study of polymerization of methyl methacrylate initiated by the charge‐transfer complex consisting of poly‐2‐vinylpyridine and liquid sulfur dioxide

Abstract: A kinetic study has been made of the polymerization of methyl methacrylate (MMA) initiated by a charge‐transfer complex of poly‐2‐vinylpyridine (electron donor) and liquid sulfur dioxide (acceptor) in the presence of carbon tetrachloride. It is concluded that the polymerization proceeds through free‐radical intermediates, as with the pyridine‐liquid sulfur dioxide complex system. The association constants K of acceptor and polymer electron donors which range widely in their molecular weight were determined spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1970
1970
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…The value obtained is 3.75 kcal/mol, which is much less than 6.7 kcal/mol as reported in literature [1] for a system similar to that of the present study but accelerated by metal complex. This confirms the advantage of charge transfer polymerization over other methods.…”
Section: Activation Energiescontrasting
confidence: 42%
See 1 more Smart Citation
“…The value obtained is 3.75 kcal/mol, which is much less than 6.7 kcal/mol as reported in literature [1] for a system similar to that of the present study but accelerated by metal complex. This confirms the advantage of charge transfer polymerization over other methods.…”
Section: Activation Energiescontrasting
confidence: 42%
“…E-mail: psts@iitm.ac.in charge transfer polymerization of MMA are summarized in Table 1. Matsuda and Ishiroshi [1] investigated kinetics initiated by transfer complex of poly-2-vinyl pyridine and liquid sulfur dioxide in the presence of carbon tetrachloride (CCl 4 ). They studied the effect of concentrations of complex, monomer and CCl 4 on the rate of polymerization and reported that both equilibrium constant and overall rate of polymerization decreased with increasing molecular weight of polymer donor.…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing interest in the initiation of polymerization of vinyl monomers such as methyl methacrylate (MMA) and vinyl chloride by the charge transfer mechanism (1)(2)(3)(4)(5). The polymerization of MMA by a compound containing a donor nitrogen atom in the presence of carbon tetrachloride (CC14) is now well established (6).…”
Section: Introductionmentioning
confidence: 99%
“…A charge-transfer mechanism for the initiation of MMA has been proposed. polymerization by charge-transfer complexes (2,3). It was observed that polymerization could be initiated by a charge-transfer complex I in the presence of carbon tetrachloride in a solvent like N, Ndimethyl formamide (DMF), dimethyl sulphoxide (DMSO), or chloroform at 30°C.…”
mentioning
confidence: 99%